Improved rovibrational constants for the v6 + v10 band of ethylene (12C2H4) by high-resolution Fourier transform infrared spectroscopy - Lebron, Gissela B. (Animo Repository, 2013)
Fourier transform infrared absorption spectrum of the ν6+ν10 combination band of 12C2H4 in the 1985-2100cm-1 region was measured at an unapodized resolution of 0.0063cm-1. The A-type ν6+ν10 band is centered at 2047.75817+/-0.00006cm-1. The rovibrational analysis performed on the band using a standard Watson's A-reduced Hamiltonian model in Ir representation yielded the most accurate set of v6+v10=1 state constants to date. Upper-state parameters inclusive of three rotational, five quartic and two sextic terms were derived from a total of 527 infrared transitions assigned and included in the final fit. The rms deviation of the fit was 0.000625cm-1.